The Influence of Intellectual Stimulation on Human Resource Performance through Self-Efficacy at PT PLN (Persero), East and North Kalimantan Distribution Main Unit - Fenti Arie Ervia; Asyhari Asyhari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the influence of intellectual stimulation on human resource performance through self-efficacy at PT PLN (Persero), East and North Kalimantan Distribution Main Unit. Intellectual stimulation, as part of transformational leadership, is believed to enhance employees' ability to think critically and solve problems creatively, which in turn can improve their self-efficacy and overall job performance. Using a quantitative approach with data collected through questionnaires distributed to employees, this research analyzes the direct and indirect effects of intellectual stimulation on performance. The findings indicate that intellectual stimulation has a significant positive effect on self-efficacy and human resource performance, with self-efficacy acting as a mediating variable. These results highlight the importance of leaders applying intellectually stimulating strategies to foster a more confident and high-performing workforce.